PENGARUH GAYA KEPEMIMPINAN TERHADAPEMPLOYEE ENGAGEMENT KARYAWAN SMKRADEN RAHMAT MOJOSARI - Yusny Muzakki Muzakki; Deddy Ahmad Fajar; Fatimah Azzahra (El-Idaarah, 2022)
The aim of the research is to examine the partial influence of leadership styleon employee engagement at Raden Rahmat Mojosari Vocational School.The type of research used is quantitative. The sample in this research wasemployees of Raden Rahmat Mojosari Vocational School, a sample of 23respondents. The analytical methods used are validity test, reliability test,classical assumption test, multiple linear regression test, hypothesis test, andcoefficient of determination. Based on the research results, it shows thatleadership style partially has a significant positive effect on employeeengagement of Raden Rahmat Mojosari Vocational School employees. Thisresult was obtained with a sig value of 0.001 < 0.05 or a tcount value of3.555 > ttable 2.086.